Administration of Archives of the General Subdivision at the Office of Water Resources, Highways and Construction Development in Lubuk Pakam - Syahputri, Juli; Nurbaiti, Nurbaiti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
Archives play an important role in administration, as part of a source of information in planning, analyzing, formulating policies, making decisions, preparing reports, evaluating, controlling and implementing accountability. So in the organization it is necessary to have a good, neat, orderly, effective and efficient filing system. With such a filing system, it can help smooth the working mechanism of all office administration activities. However, if archive management is not handled properly, this can hinder the smooth running of organizational activities and can even result in a waste of thought, energy and time.